(untitled) (Iranian Journal of Kidney Diseases, 2020)
Introduction. Contrast induced nephropathy (CIN), a well-known complication of using radio contrast media, dramatically increases the likelihood of patient morbidity and mortality following coronary angiography. As there is no specific treatment for CIN, prevention could be the best strategy to address this issue. Since now, the only approved preventing strategy was hydration with normal saline while antioxidant agents as a new yet unapproved remedy for this purpose could be applied .The present study was conducted to examine the effect of alpha tocopherol in CIN prevention. Methods. This prospective controlled trial was carried out on 201 patients with chronic kidney disease (eGFR < 60 cc/min) underwent coronary angiography. We assigned three groups of CKD patients: 72 patients who received prophylaxis administration with isotonic saline (Group A), 66 patients with isotonic saline plus N-acetylcysteine (1200mg twice a day) for 2 days (Group B) and 63 patients who received isotonic saline plus daily alpha tocopherol (600 IU once daily from one day before till 2 days after angiography) for 4 days (Group C). The contrast media in all three groups was nonionic iso-osmolal agent, Visipaque. Results. Even though CIN didn’t developed in any of the three aforementioned groups but there was statistically significant reduction in eGFR from baseline in all three groups (P < .001). Moreover, We found no statistically significant difference in GFR reduction between three studied groups. Conclusion. Administration of alpha tocopherol has no additive beneficial effect over isotonic saline in CIN prevention in CKD patients.